Impact of postoperative morbidity on the prognosis of patients with hepatocellular carcinoma after laparoscopic liver resection: a multicenter observational study - Shiye Yang; Haishun Ni; Aixian Zhang; Jixiang Zhang; Hong Zang; Zhibing Ming (Scientific Reports)
Abstract The long-term impact of postoperative morbidity following laparoscopic liver resection for hepatocellular carcinoma is unclear. This study aimed to investigate whether the prognosis of hepatocellular carcinoma patients were affected by postoperative morbidity after laparoscopic liver resection. Hepatocellular carcinoma patients who underwent curative-intent laparoscopic liver resection were included. Risk factors of 30-day morbidity were identified using logistic regression analysis. Early (≤ 2 years) and late (> 2 years) recurrence rates, overall survival, and time to recurrence were compared among patients with and without postoperative morbidity. Independent prognostic factors of overall survival and time to recurrence of these patients were investigated using Cox regression analysis. This study included 420 patients, 147 (35%) of whom experienced postoperative morbidity. Diabetes mellitus, cirrhosis, portal hypertension, Child-Pugh grade B, multiple tumors, poor tumor differentiation and intraoperative blood transfusion were risk factors of postoperative morbidity. Patients with postoperative morbidity had higher early and late recurrence rates than those without postoperative morbidity (38.8% vs. 22.4%, P = 0.001; 50% vs. 25.5%, P = 0.001). Postoperative morbidity was associated with decreased overall survival (median: 54.5 months vs. not reached, P < 0.001) and time to recurrence (median: 36.4 vs. 68.2 months; P < 0.001). Postoperative morbidity resulted in a 43% and 92% higher risk of long-term mortality (HR 1.43; 95% CI 1–2.03; P = 0.048) and recurrence (HR 1.92; 95% CI 1.41–2.62; P < 0.001). For hepatocellular carcinoma patients undergoing laparoscopic liver resection, long-term oncologic outcomes are adversely affected by postoperative morbidity. Therefore, it is of great importance for surgeons to prevent and manage postoperative morbidity.